Increasing Ability to Understand Fairy Tale Through Directed Reading Thinking Activity (DRTA) Strategy - Titin Setiartin (STKIP Singkawang, 2018)
The DRTA strategy is basically designed for group reading teaching. This strategy has received great attention from language teachers over the last two decades because of its ease and emphasis on developing high-minded processes. In addition, DRTA involves an active understanding and exchange of ideas among learners. Effective also in directing the social dynamics of learning groups of learners. Individual and group predictions about the content of reading are developed on the basis of individual backgrounds and information contained in the text. This strategy requires teachers to create hypotheses and make predictions about the content of the reading. Group dynamics will generate predictions and provide opportunities for learners to link these predictions with reading content. The purpose of this study is to describe the effectiveness of DRTA strategy in reading comprehension learning; describe the improvement of the ability of learners in reading fairy tales. The result of the research can be known based on the gain index of the initial and final test of the experimental class and control class, there is an increasing difference between the learning by using DRTA strategy and the learning using conventional strategy from percentage gain improvement in the experimental class higher than the control class. While the gain index of the experimental class is 0.57 (including the medium category) with the lesson using the DRTA strategy and for the control class with the gain index of 0.45 (including the medium category) with the reading comprehension learning conventional strategy. From the difference of gain, index can be concluded that there is a difference of understanding between learners who learn by using DRTA strategy with students who study conventionally. Between the two experimental classes, the average value of learners who learn to use DRTA is higher than that of learners who learn to use conventional learning. Constructivists view that learning is a process of assimilating and connecting the experience or material learned with the understanding it has for the understanding to develop.